2020
DOI: 10.3390/ijfs8040061
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Carbon Risk and the Cost of Debt: Evidence from the European Market

Abstract: The ever-increasing attention towards climate change has led to investigate the economic and financial impact of environmental risk. In this scenario, we aimed at investigating the relationship between a specific component of environmental risk, namely the so-called carbon risk, and the cost of debt. This research is motivated by the fact that few studies have focused on the aforementioned relationship. We fill this gap by using a sample of companies listed on the Eurostoxx 600 Index. Our results evidence a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…Second, inferences drawn from prior studies suggest that environmental regulation increases heavy-polluting firms' environmental liabilities and environmental risks (Schneider, 2008), making debt financing more difficult and costly (Caragnano et al, 2020;Pizzutilo et al, 2020;Ding et al, 2021). In the Chinese capital market, bank loans are the main source of external finance for corporations, due to the immature stock and bond market (Cull and Xu, 2000;Shen et al, 2015).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, inferences drawn from prior studies suggest that environmental regulation increases heavy-polluting firms' environmental liabilities and environmental risks (Schneider, 2008), making debt financing more difficult and costly (Caragnano et al, 2020;Pizzutilo et al, 2020;Ding et al, 2021). In the Chinese capital market, bank loans are the main source of external finance for corporations, due to the immature stock and bond market (Cull and Xu, 2000;Shen et al, 2015).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The environment is ever-changing, uncertain, and unpredictable (Sharma et al, 2021a). Stringent environment regulation induces heightened environmental uncertainty (Lanoie et al, 2008) by enhancing the heavypolluting firms' environmental risks (Falk and Wee, 2015;Liu X. et al, 2021), making debt financing more difficult and costly (Caragnano et al, 2020;Pizzutilo et al, 2020;Ding et al, 2021). In addition, to achieve the social goal of sustainable development, non-heavy-polluting industries such as new energy industries, typically receive more subsidies (Qiao and Fei, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We also control for firm debt, DEPT, calculated by total debt to total assets ratio (Rubino and Napoli 2020). Finally, we control for market to book ratio, MTB, measured by dividing market capitalization on the net book value (Pizzutilo et al 2020). Based on the prior studies concerning ESG, it is indicated that ESG is industry specific (Mănescu 2011).…”
Section: Research Modelsmentioning
confidence: 99%
“…Scholars have also demonstrated that lenders pay particular attention to the exposure to environmental risk in evaluating the overall firms' risk profile (Herbohn et al, 2019; Jung et al, 2018; Raimo et al, 2021). Other studies stressed that costs arising from environmentally irresponsible behaviours not compliant with the required standards and regulations can negatively affect the ability to repay debts and the probability of default (Li et al, 2014; Pizzutilo et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%